2020
DOI: 10.1044/2019_jslhr-19-00087
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Production in Mandarin-Speaking Children: Effects of Language Ability and Elicitation Method

Abstract: Purpose We compared the narrative production in Mandarin-speaking children at risk (AR) for developmental language disorder (DLD) and typically developing (TD) controls to address two goals: (a) further our understanding of the Mandarin DLD phenotype and (b) examine the role of elicitation method in differentiating AR from TD. Method Twenty-one AR children and 21 age- and nonverbal IQ–matched peers produced two stories from the Multilingual Assessment I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…The Mandarin adaptation involved several rounds of translation and revision and the incorporation of Mandarinspecific examples to explain the rating scale. The Mandarin ITALK has been used in previous studies of Mandarin-English bilingual children (Sheng et al, 2011(Sheng et al, , 2014 as well as monolingual Mandarin-speaking children (Sheng et al, 2020). English and Mandarin oral language proficiency was rated on a 0-5 scale in the domains of vocabulary, sentence length, speech intelligibility, listening comprehension, and grammatical proficiency.…”
Section: Methodsmentioning
confidence: 99%
“…The Mandarin adaptation involved several rounds of translation and revision and the incorporation of Mandarinspecific examples to explain the rating scale. The Mandarin ITALK has been used in previous studies of Mandarin-English bilingual children (Sheng et al, 2011(Sheng et al, , 2014 as well as monolingual Mandarin-speaking children (Sheng et al, 2020). English and Mandarin oral language proficiency was rated on a 0-5 scale in the domains of vocabulary, sentence length, speech intelligibility, listening comprehension, and grammatical proficiency.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the AR group exhibited poorer abilities in story structures, sentence complexity, and lexical diversity than did the TD group. In previous studies about DLD, SLI, and LI, researchers did not reach a conclusion on grammatical errors and number of complex sentences as evident measures for identifying Mandarin-speaking children with DLD (Sheng et. al., 2020; Torng and Sah, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…Limited studies have addressed the language abilities of Mandarin-speaking children with DLD. Sheng et al (2020) studied narrative production in Mandarin-speaking children at risk (AR) for DLD and typically-developing (TD) controls who were aged from 3 years and 6 months old to 6 years and 5 months old. They found that the AR group exhibited poorer abilities in story structures, sentence complexity, and lexical diversity than did the TD group.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Urdu and Cantonese versions of MAIN have been used to assess bilingual children with and without suspected language impairments, and show promise to differentiate between the two groups (Chan et al, 2018;Chan et al, under revision). Another example of using MAIN in research is Sheng et al (2020), where there is evidence for differentiation between Mandarin-speaking children at risk for DLD and typically developing controls using Mandarin MAIN.…”
Section: Discussionmentioning
confidence: 99%